Konseling Individu Berbantuan Metode Cinema Therapy untuk Mengatasi Self Acceptance - Elvin Monika Putri; Neni Noviza; Lena Marianti (Scidacplus, 2025)
This study aims to determine the description of Self Acceptance in beneficiaries with physical disabilities and to determine the application of individual counseling assisted by the Cinema Therapy Method in overcoming Self Acceptance in beneficiaries with physical disabilities at the Budi Perkasa Center in Palembang. This study uses a qualitative research method with a field research type. The subjects in this study were three beneficiaries with physical disabilities and one social worker at the Budi Perkasa Center in Palembang who were selected using the purposive sampling technique. In order to achieve this goal, the data collection technique in this study used interviews, observation, and documentation techniques, which were carried out in 4 meetings. The results of this study indicate that before the application of individual counseling assisted by the Cinema Therapy method, the description of self-acceptance in beneficiaries with physical disabilities at the Budi Perkasa Center in Palembang was still very clear, which was indicated by the beneficiaries still displaying behaviors that indicate aspects of self-acceptance, such as thinking negatively about themselves and not being able to accept themselves. Furthermore, after the implementation of individual counseling assisted by the Cinema Therapy method was carried out, it showed that self-acceptance in children with disabilities was able to accept themselves well without any rejection in themselves, able to socialize without any shame, and always think positively about their physical condition. Individual counseling assisted by the Cinema Therapy method to overcome Self-Acceptance in people with physical disabilities using three stages, namely the initial stage, the middle stage, and the final stage.